Chemical etching of CdTe, CdₓHg₁-ₓTe, ZnₓCd₁-ₓTe and Te in the HNO₃-HCl-citric acid - Tomashik, Z.F.; Bilevych, Ye.O.; Feichuk, P.I.; Tomashik, V.M. (Functional Materials, 2005)
The peculiarities of CdТе, CdTe, CdₓHg₁-ₓTe, ZnₓCd₁-ₓTe and Те single crystals dissolution in the solutions of HN0₃-HCl-citric acid system are investigated and the surfaces of equal etching rates (Gibbs diagrams) are constructed. The limiting stages of dissolution process and regions of polishing solutions for these semiconductors are determined. Increasing of ZnТе contents in the Cd₁-ₓZnₓТе solid solutions has been shown to result in a linear increasing of dissolution rate.